2016
DOI: 10.1007/978-1-4939-3771-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Human Cancer Cell Proliferation, Invasion, and Micrometastasis in a Zebrafish Xenogeneic Engraftment Model

Abstract: The xenograft model, using the early life stages of the zebrafish, allows imaging of tumor cell behavior both on a single cell and whole organism level, over time, within a week. This robust and reproducible assay can be used as an intermediate step between in vitro techniques and the expensive, and time consuming, murine models of cancer invasion and metastasis.In this chapter, a detailed protocol to inject human cancer cells into the blood circulation of a zebrafish embryo is described; the engraftment proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Experiments were performed on zebrafish larvae before the onset of independent feeding, according to Dutch animal welfare regulation. Experimental procedures and analyses were previously described in detail [57] (also see Document S1: ARRIVE Guidelines Checklist). A673 cells expressing shRNA-silencing RON (Group 1-experimental group) or the non-silencing control (Group 2-control group) together with GFP reporter protein were implanted into the duct of Cuvier of larvae 2 days post fertilization.…”
Section: Zebrafish Xenograft Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were performed on zebrafish larvae before the onset of independent feeding, according to Dutch animal welfare regulation. Experimental procedures and analyses were previously described in detail [57] (also see Document S1: ARRIVE Guidelines Checklist). A673 cells expressing shRNA-silencing RON (Group 1-experimental group) or the non-silencing control (Group 2-control group) together with GFP reporter protein were implanted into the duct of Cuvier of larvae 2 days post fertilization.…”
Section: Zebrafish Xenograft Modelmentioning
confidence: 99%
“…A673 cells expressing shRNA-silencing RON (Group 1-experimental group) or the non-silencing control (Group 2-control group) together with GFP reporter protein were implanted into the duct of Cuvier of larvae 2 days post fertilization. Four days after implantation, tumor burden was analyzed by automated image analysis of GFP-fluorescent objects per zebrafish area as described [57].…”
Section: Zebrafish Xenograft Modelmentioning
confidence: 99%
“…For melanoma, a presently on-going phaseI/II clinical trial of Leflunomide combined with vemurafenib is the first to arise from initial screen in zebrafish. To study human cancer metastasis, our group generated a xenotransplantation model of experimental micrometastasis [60,61] . Human tumour cells engrafted into the blood circulation of 2-day-old zebrafish embryos induce angiogenesis and form micrometastasis sustained by neutrophils and macrophages, nearby hematopoietic sites [60] .…”
Section: Zebrafish Xenograft As a Model To Study Cancermentioning
confidence: 99%
“…In particular, tumour-induced angiogenesis, metastasis formation and relative chemical approaches to inhibit these processes have been studied using zebrafish as a xenotransplantation model, complementing current knowledge developed through the use of in vitro and other in vivo models [62] . Upon localised or haematogenous engraftment of cancer cells, zebrafish xenografts allow qualitative and quantitative assessment of tumour burden and tumour-microenvironment interaction, representing a powerful pre-clinical model to unravel cancer mechanisms and to develop new therapeutic strategies [61] . In particular, alongside murine models, the use of PDXs in zebrafish has the potential to be used in personalised medicine [63][64][65][66] , with the advantage of requiring less tumour material and shorter times for the monitoring of tumour development [57] .…”
Section: Zebrafish Xenograft As a Model To Study Cancermentioning
confidence: 99%
“…showed that a human breast cancer cell line derived from a metastatic patient can engraft and proliferate in a zebrafish embryo. Importantly, a zebrafish ligand could elicit a CXCR4‐mediated response in human cancer cells (Tulotta et al., ). Xenotransplantations are however complicated by differences in body temperature between zebrafish (28C) and humans (37C), and interspecies compatibilities.…”
Section: Modeling Metastasis and Visualizing Tumor–microenvironment Imentioning
confidence: 99%